Incremental yield and cost of urine Determine TB-LAM and sputum induction in seriously ill adults with HIV - Boyles, Tom H. (Int J Infect Dis, 2018)
BACKGROUND: Tuberculosis is a major cause of mortality among HIV-infected inpatients, and the World Health Organization (WHO) recommends an algorithm to improve diagnosis. The urine lateral flow lipoarabinomannan (LAM) and sputum Xpert MTB/RIF tests are promising tools, but the optimal diagnostic algorithm is unclear. METHODS: This prospective cohort study enrolled HIV-positive inpatients with cough and WHO danger signs. The Xpert MTB/RIF test and mycobacterial culture were performed on sputum using sputum induction when necessary, and the LAM test was performed on stored urine. Tuberculosis was diagnosed by culture from any site. The diagnostic accuracy and costs of testing were determined for single and combined tests. RESULTS: Tuberculosis was confirmed in 169 of 332 patients (50.9%). The yield of LAM, Xpert MTB/RIF on spontaneous sputum (Xpert Spot), and Xpert MTB/RIF on spontaneous or induced sputum (Xpert SI) was 35.5%, 23.1%, and 90.5%, respectively. When LAM was placed before Xpert Spot and Xpert SI in an algorithm, the yield was 50.9% and 92.3%, respectively. Adding culture to Xpert MTB/RIF only increased the yield by 1.2% and 2.7%, respectively. Use of the LAM test reduced costs. CONCLUSIONS: Sputum induction is important to increase the yield of Xpert MTB/RIF for seriously ill patients with HIV and cough. LAM testing has little effect on yield when sputum induction is available, but reduces costs and may have other benefits.